Analysis of DNA Methylation Status of the OsSOS1 Gene under Salt Stress in Rice - Hoa, Pham Quynh; Thanh, Nguyen Dinh; Phuc, Do Thi (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: OsSOS1 is a Na + /H + transporter presented on cellular membranes which plays a crucial role in salt response in plant through SOS pathway. DNA methylation is an inherited and reversible epigenetic modification which affects directly on the regulation of gene expression, and therefore might effect on salt tolerance in plant. In this study, McrBC – an endonuclease which is sensitive to methylcytosine – was used to detect DNA methylation status in some regions of the OsSOS1 gene in two rice cultivars: a salt sensitive cultivar Nipponbare and a salt tolerant cultivar Pokkali under saline condition. McrBC-PCR revealed two hypermethylation regions in the middle of OsSOS1 gene while the other two showed hypomethylation. Furthermore, the methylation status was the same in shoot and in root tissues, and had no significant change under salt condition compared to control condition in both investigated cultivars. Result of bisulfite sequencing showed that the hypermethylation only occurred in CpG sites but not CHG and CHH contexts. Keywords: DNA methylation, OsSOS1 , rice.